Broadband cable tv access networks: from technologies to applications - Ovadia, Shlomo
Next-generation CATV systems: architecture, protocols, technologies, and applications. *Cable modems and digital set-top boxes: architecture and operation *HFC and its competitors: DSL, FTTL, DBS, and MMDS *Evolving from two-way HFC networks to next-generation DWDM access *Key applications: EPGs, IPPV, VOD, web browsing, e-mail, e-commerce, and more Broadband cable TV networks are undergoing a massive transformation, from simply broadcasting analog TV channels to providing sophisticated, two-way interactive services such as high-speed Internet access and video-on-demand. Now, one of the field's leading experts reviews the technologies, protocols, applications associated with the CATV revolution, and previews the migration path from today's two-way hybrid fiber/coax networks to the awesome capacities of tomorrow's DWDM fiber networks. Coverage includes: *HFC cable networks vs. the competition: DSL, FTTL, DBS, and MMDS *Key fiber-optics transmission technologies: directly and externally modulated laser transmitters, optical receivers, and Erbium-doped optical fiber amplifiers (EDFAs) *Architecture of DWDM access networks *Hardware architecture and operation of digital set-top boxes and cable modems *Software architecture and applications for digital set-top boxes Ovadia offers in-depth analyses of single and multiple-wavelength fiber-optics transmission impairments over HFC and DWDM networks, and presents the emerging two-way DWDM network architecture. Finally, he discusses the DOCSIS cable modem protocol, as well as key set-top box's applications such as electronic program guides (EPGs), video-on-demand (VOD), Internet-based applications such as e-mail, and e-commerce. Whether you're an engineer, scientist, cable professional, manager, or investor, if you want to understand where cable is headed, you need Cable TV Access Networks: From Technologies to Applications.